Between Exile and Exodus : Argentinian Jewish Immigration to Israel, 1948-1967 - Klor, Sebastian (Book collections on Project MUSE., 2017)
Between exile and exodus : Argentinian Jewish immigration to Israel, 1948-1967 examines the case of the 16,500 Argentine Jewish immigrants who arrived in Israel during the first two decades of its existence (1948-1967). Based on a thorough investigation of various archives in Argentina and Israel, author Sebastian Klor presents a sociohistoric analysis of that immigration with a comparative perspective. Although many studies have explored Jewish immigration to the State of Israel, few have dealt with the immigrants themselves.